Disparities in Gynecological Malignancies - Chatterjee, Sudeshna; Gupta, Divya; Caputo, Thomas A.; Holcomb, Kevin (Frontiers in Oncology, 2016)
Objectives: Health disparities and inequalities in access to care among different socioeconomic, ethnic, and racial groups have been well documented in the U.S. healthcare system. In this review, we aimed to provide an overview of barriers to care contributing to health disparities in gynecological oncology management and to describe site-specific disparities in gynecologic care for endometrial, ovarian, and cervical cancer. Methods: We performed a literature review of peer-reviewed academic and governmental publications focusing on disparities in gynecological care in the United States by searching PubMed and Google Scholar electronic databases. Results: There are multiple important underlying issues that may contribute to the disparities in gynecological oncology management in the United States, namely geographic access and hospital based-discrepancies, research-based discrepancies, influence of socioeconomic and health insurance status, and finally the influence of race and biological factors. Despite the reduction in overall cancer-related deaths since the 1990s, the 5-year survival for Black women is significantly lower than for White women for each gynecologic cancer type and each stage of diagnosis. For ovarian and endometrial cancer, black patients are less likely to receive treatment consistent with evidence-based guidelines and have worse survival outcomes even after accounting for stage and comorbidities. For cervical and endometrial cancer, the mortality rate for black women remains twice that of White women. Conclusions: Health care disparities in the incidence and outcome of gynecologic cancers are complex and involve biologic factors as well as racial, socioeconomic and geographic barriers that influence treatment and survival. These barriers must be addressed to provide optimal care to women in the U.S. with gynecologic cancer.